MODERN PEDAGOGICAL TECHNOLOGIES IN DEVELOPING STUDENTS’ SPEAKING SKILLS IN ENGLISH LESSONS - Mo‘minova Sevinch (TADQIQOTLAR, 2026)
ANNOTATION This article examines the role of modern pedagogical technologies in developing students’ speaking skills in English lessons. The study highlights the importance of communicative competence in foreign language learning and analyzes effective teaching methods that encourage active participation of students. Particular attention is given to interactive teaching methods, communicative language teaching, digital technologies, gamification, and project-based learning. The article concludes that the use of modern pedagogical technologies significantly improves students’ motivation, confidence, and ability to communicate in English.